(untitled) (Revista de Estudos da Linguagem, 2020)
Resumo: Este trabalho pretende analisar de um ponto de vista cognitivo e discursivo o uso de metáforas e blends multimodais sobre política presentes em um blog político brasileiro. Nesse sentido, interessa avaliar o modo pelo qual diferentes sistemas semióticos coexistem na construção de processos constitutivos desse gênero digital, a exemplo de recursos verbais e imagéticos. Isso possibilita um aprofundamento do conhecimento acerca das crenças, valores e ideologias políticas que caracterizam os discursos sobre democracia. Além disso, este estudo permite também avaliar como o desenvolvimento das tecnologias de informação e comunicação, a exemplo da blogosfera, engendram novas formas de discussão e de participação política, viabilizando, sobretudo, a produção de novas estratégias cognitivas e discursivas, através da exploração de diferentes recursos semióticos. Nesse sentido, as operações de metaforização e/ou de mesclagem, enquanto constitutivas do modo de pensar, agir e se comunicar dos seres humanos emergem como objetos privilegiados de uma abordagem cognitivo-discursiva dos blogs políticos, em função de sua recorrência e relevância nesse(s) gênero(s). Assim, os blogs políticos são concebidos como espaços semióticos que emergem da interação entre os sujeitos e as novas mídias digitais, produzindo sentido através da integração de diferentes recursos semióticos. Essa interação engendra processos metafóricos e/ou mesclagens representativas do modo pelo qual esses sujeitos, enquanto cidadãos, experienciam o espaço público e agem politicamente através do discurso, posicionando-se, debatendo e, por vezes, manipulando as opiniões. Palavras-chave: metáforas e blends multimodais; cognição; discurso; blogs políticos. Abstract: This work intends to analyze from a cognitive and discursive point of view the use of multimodal metaphors and blends about politics in Brazilian political blogs. It is interested in evaluating the way in which different semiotic systems coexist in the construction of constitutive processes of this digital genre with special reference to verbal and imaginary resources. It is meant to enhance knowledge about the beliefs, values and political ideologies that characterize the discourses on democracy. Moreover, it allows us to evaluate how the development of information and communication technologies has crafted new forms of discussion and political participation by enabling new cognitive and discursive strategies. The use of metaphors and blends, while constitutive of the way human beings think, act and communicate, can be accounted for as recurrent framings in political blogs from a cognitive-discursive approach. Hence, that political blogs can be dealt with as semiotic mental spaces that emerge from the interaction between subjects and new digital media, producing meaning through the conceptual integration of different semiotic resources. This interaction engenders metaphorical and blending processes as representations of how these subjects, as citizens, experience the public space and act politically through discourse by taking stances, debating and sometimes manipulating opinions. Keywords: multimodal metaphors and blends; cognition; discourse; political blogs. Abstract: This work intends to analyze from a cognitive and discursive point of view the use of multimodal metaphors and blends about politics in Brazilian political blogs. It is interested in evaluating the way in which different semiotic systems coexist in the construction of constitutive processes of this digital genre with special reference to verbal and imaginary resources. It is meant to enhance knowledge about the beliefs, values and political ideologies that characterize the discourses on democracy. Moreover, it allows us to evaluate how the development of information and communication technologies has crafted new forms of discussion and political participation by enabling new cognitive and discursive strategies. The use of metaphors and blends, while constitutive of the way human beings think, act and communicate, can be accounted for as recurrent framings in political blogs from a cognitive-discursive approach. Hence, that political blogs can be dealt with as semiotic mental spaces that emerge from the interaction between subjects and new digital media, producing meaning through the conceptual integration of different semiotic resources. This interaction engenders metaphorical and blending processes as representations of how these subjects, as citizens, experience the public space and act politically through discourse by taking stances, debating and sometimes manipulating opinions.Keywords: multimodal metaphors and blends; cognition; discourse; political blogs.